Planar Monopoles with Different Radiator Shapes for UWB Body-Centric Wireless Communications - Y. Y. Sun; S. W. Cheung; T. I. Yuk (Journal of Engineering)
This paper presents a study on the performances of a group of planar monopoles using radiators of different shapes, such as triangle, rectangle, square, annual ring, circle, horizontal ellipse, vertical ellipse, pentagon, and hexagon, for ultra-wideband (UWB) body-centric wireless communications. The planar monopoles have the radiators with microstrip-fed line printed on one side of the substrate and a ground plane on the other side. Simulation studies show that, among these monopoles, the horizontal elliptical, vertical elliptical, and hexagonal monopoles have better overall performances in terms of bandwidth, gain, efficiency, and radiation pattern in free space. A solid-body phantom mimicking human tissue is used for studies of these three monopoles for body-centric communications. Simulated and measured results of these monopoles on the phantom show that the horizontal elliptical monopole achieves the widest impedance bandwidths, highest average peak gain and efficiency, least path loss, best fidelity, and good radiation pattern, making it a good candidate for UWB body-centric wireless communications.